Mendesain Identitas, Mendorong Pertumbuhan UMKM:Inovasi Kemasan dan Penyuluhan Masyarakat Untuk Usaha Hidroponik Selada - Aisyah, Ulfi; Lestari , Dian; Nursyah, Dinayah RamadanDinayah; Hasan, Moh. Albi; Akhmad Jufri (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Abstract: Banyumulek Village is an area that has long been known as a center for traditional pottery production with high cultural value. This village is slowly opening itself up to innovation in the modern agricultural sector. Kopmas Farm as an object of devotion, as a medium for socializing modern agriculture, namely hydroponic lettuce by strengthening product identity and marketing strategies. Although the product is of high quality, there are still obstacles in packaging design, branding, and digital promotion. Kopmas Farm innovation is focused on developing closed packaging that is designed to maintain the freshness of hydroponic lettuce. This packaging is chosen because it is more hygienic, practical, and able to reduce the risk of spoilage during shipping. Community service is carried out to provide information to the Banyumulek community who already have and do not have a hydroponic farming business and to provide education to hydroponic lettuce farmers in the NTB area. The results of the innovation were used during the Eid al-Adha promotion, successfully increasing sales by 300 pcs and attracting the attention of the local market. The extension activities were very well received by the Banyumulek village community with high enthusiasm from various parties who contributed, active participation, and many questions about design and digital promotion strategies. The results of monitoring 2 weeks after the activity with the specified indicators showed that the extension was successful. Keywords: Packaging Innovation, Marketing, Community Extension